Testing and modeling the behavior of sandwich lightweight panels against wind and seismic loads. (15th November 2018) - Assaad, Joseph; Chakar, Elie; Zéhil, Gérard-Philippe
Highlights: Assessing shear transfer between panels through tongue-and-groove joints. Measuring pullout and shear forces of dowels embedded in EPS-based concrete. Correlating density of EPS-based concrete to panel behavior in service conditions. Predictive charts for safety factor as a function of type/magnitude of lateral loading. Abstract: The behavior of non-structural sandwich lightweight panels against wind and seismic loadings is not well understood. Such panels are typically composed of two calcium-silicate board (CSB) wythes separated by a core infill made of expanded polystyrene lightweight concrete (LWC). This paper provides understanding regarding the mechanisms of panel connectivity by tongue-and-groove, including transfer of forces through steel dowels to the existing structure. Series of LWC mixtures having 470 to 975 kg/m 3 density were tested using suitably established testing procedures to determine the flexural strength, core shear strength, interfacial bond between LWC and CSB, and pullout forces transmitted through the steel dowels. Special emphasis is placed on modeling the effect of wind and seismic loads on a 3.6 × 3 m 2 partition wall constructed using LWC sandwich panels. The highest stresses and deformations generated from the model are compared to those determined experimentally, which allowed establishing different charts that can predict the safety factors as a function of LWC density and type/magnitude of the lateral loading applied.